Comprehensive lipidomics in apoM-/- mice reveals an overall state of metabolic distress and attenuated hepatic lipid secretion into the circulation. (20th September 2020) - Shi, Yuanping; Lam, Sin Man; Liu, Hong; Luo, Guanghua; Zhang, Jun; Yao, Shuang; Li, Jie; Zheng, Lu; Xu, Ning; Zhang, Xiaoying; Shui, Guanghou
Abstract: Apolipoprotein M (apoM) participates in both high-density lipoprotein and cholesterol metabolism. Little is known about how apoM affects lipid composition of the liver and serum. In this study, we systemically investigated the effects of apoM on liver and plasma lipidomes and how apoM participates in lipid cycling, via apoM knockout in mice and the human SMMC-7721 cell line. We used integrated mass spectrometry-based lipidomics approaches to semiquantify more than 600 lipid species from various lipid classes, which include free fatty acids, glycerolipids, phospholipids, sphingolipids, glycosphingolipids, cholesterol, and cholesteryl esters (CEs), in apoM -/- mouse. Hepatic accumulation of neutral lipids, including CEs, triacylglycerols, and diacylglycerols, was observed in apoM -/- mice; while serum lipidomic analyses showed that, in contrast to the liver, the overall levels of CEs and saturated/monounsaturated fatty acids were markedly diminished. Furthermore, the level of ApoB-100 was dramatically increased in the liver, whereas significant reductions in both ApoB-100 and low-density lipoprotein (LDL) cholesterol were observed in the serum of apoM -/- mice, which indicated attenuated hepatic LDL secretion into the circulation. Lipid profiles and proinflammatory cytokine levels indicated that apoM -/- leads to hepatic steatosis and an overall state of metabolic distress. Taken together, these results revealed that apoM knockout leads to hepatic steatosis, impaired lipid secretion, and an overall state of metabolic distress.